Stylistic Configuration of Modern English Young Adult Literature - Bekzhanova, Zhazira; Ayazbayeva, Aliya; Bulegenova, Indira; Zhabigenova, Gulnara (International Journal of Psychosocial Rehabilitation, 2020)
The article presents a literary study of modern young adult prose in English. Stylistic and interpretative text analysis shows that this group of literary works has its own distinctive style. This style is not opposed to classical belles-lettres. Actually, it has the same wide arsenal of devices and expressive means. At the same time, youngsters’ literary works are characterized by some youth colloquial communicative features typical for this group only. Literary stylistic devices themselves reflect specific features of youth language. These facts prove that it is necessary to single out young adult literature as a separate functional substyle as well as to provide precise parameters and linguistic characteristics that define it. Besides, the authors revealed the following categories of stylistic means and literary devices of youth literature: narrative techniques, specific lexical stylistic devices, carnivalization of values, and emblems and symbols of youth culture. For this purpose, the authors chose and analyzed three popular youth novels that have been published recently. The analysis showed that dominant narrative techniques include interior monologues, first- and second-person points of view in the text, familiarity of the author with the audience, short communicative distance, and special lexical stylistic devices such as slang epithets, slang metaphors, etc. Carnivalization of values is not restricted to certain language means. It involves youth humor, sometimes rather violent and unexpected. This feature usually radically changes the understanding of common traditional values in the society. Emblems and symbols include words that denote concepts of modern youth life. The age of the author, audience, and characters is also considered a special factor that influences the stylistic characteristics of a literary work. The results of the research can be of great use for the development of literary theory, stylistics, and text analysis.